Preferensi Jarak Personal Pengunjung Mall Nipah Makassar - Suwarni, Saskia Pratiwi; Nurhikmayanti, Nurhikmayanti; Syuaib, Mayaddah (TIMPALAJA : Architecture Student Journals, 2023)
Abstract_ Basic human behavior because of the impulse from within. A business because of a need. So that behavior occurs because of the drive to fulfill needs. It can be concluded that behavior is an activity or human activity that arises due to a stimulus, both of which can be observed directly or indirectly. behavior is an awareness of the social structure of people, a dynamic collective movement in the time of Clovis Heimsath (1988). Human behavior is understood as forming architecture but can also shape human behavior. As has been stated by Winston Churchill (1943) in Laurens (2004), “We shape our buildings; then they shape us.” Humans build buildings to fulfill their needs, and then the buildings shape the behavior of humans living there. Buildings designed by humans that were originally built to fulfill human needs affect how humans live social life and the values in life. This concerns the stability between architecture and society, where both live in environmental harmony. Nipah Mall is a family mall with an open-air concept to provide all the family’s needs in one place, such as a place to shop and a place to play. This building is based on the principles of green building design. The interesting part of this building is that is made with many openings to produce a natural and energy-efficient concept